2017
DOI: 10.3151/jact.15.558
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strengthening Performance of Post-tensioned UFC Panel on Reinforced Concrete Beams

Abstract: The ultra high strength fiber reinforced concrete (UFC) is an advanced cementitious material which grants the high performances in strength, durability, and ductility. Because of these high performances, in this study, it was applied into the new idea for shear strengthening to RC beams, namely the post-tensioned UFC panel. It is the prefabricated UFC panel prestressed by some prestressing force. Three parameters (i.e., the number of post-tensioned UFC panel, the amount of prestressing rods, and the prestressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Sugano et al (2007) indicated the applicability of UFC to earthquake resistant structures based on cyclic loading tests of a pier model. Limpaninlachat et al (2017) proposed a method for the evaluation of load-carrying capacity for a beam, with UFC panels placed on both side-surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Sugano et al (2007) indicated the applicability of UFC to earthquake resistant structures based on cyclic loading tests of a pier model. Limpaninlachat et al (2017) proposed a method for the evaluation of load-carrying capacity for a beam, with UFC panels placed on both side-surfaces.…”
Section: Introductionmentioning
confidence: 99%